Sentidos de família em campanhas publicitárias: análise do contrato comunicativo interseccional do Ministério da Mulher, da Família e dos Direitos Humanos - Mustafé, Isabella Szabor Machado (2022)
The research investigates the discursive strategies articulated to the meanings of family in three advertising campaigns of the Ministry of Women, Family and Human Rights (MMFDH), launched between 2019 and 2020. Given the centrality of the family in the federal governmental management, it is investigated how the implicit communication policy of public utility advertising of the MMFDH expresses or positions itself as an enunciator and builds a place for the recipient to treat the family, with class, gender, race, territoriality and deficiency bem defined and limited. By having meanings and strategies as main axes, it is believed that the analysis of the message can be operationalized by the communicative contract of Verón (1985; 2004) articulated to the intersectional perspective, especially intersectionality as an analytical tool (COLLINS; BILGE, 2021), based on an “intersectional communicative contract”. Advertising and publicity are seen as persuasive communication (GOMES, 2010), considering a hybrid concept of public utility advertising (BRAZIL, 2017) and public interest advertising (SALDANHA, 2019), as well as advertising as a visibility instrument, credibility and creation. of a public image of the government, and the communicational strategy of the State in the dispute of versions (WEBER, 2011). There is the establishment of intersectional communicative contracts of hate and control, contrary to what is expected of public communication, and parallel contracts, which indicate traces of permanent campaign communication. Elements of the enunciative strategies and basic axes of the alt-right are appreciated, such as libertarianism and religious fundamentalism, and the constant transfer of responsibility of the State by suggesting a behavior, close to familism.